Chronic unilateral vestibular hypofunction: a qualitative study exploring the full spectrum of symptoms and impacts through the ICF framework - Karabulut, Mustafa; Avci, Hamide; Yalçınkaya, Eda; Kimman, Merel; Viechtbauer, Wolfgang; Mohamad, Alfarghal; Van Rompaey, Vincent; Guinand, Nils; Fornos, Angélica Perez; Özlüoğlu, Levent; Özgirgin, Osman Nuri; van de Berg, Raymond (Frontiers in Neurology, 2025)
AimTo explore the full spectrum of symptoms and impacts associated with chronic unilateral vestibular hypofunction (UVH), and to assess whether these symptoms and impacts are fully covered by patient-reported outcome measures (PROMs) within the International Classification of Functioning, Disability and Health (ICF) framework.MethodsA qualitative study was conducted using semi-structured interviews, which were recorded, transcribed, and analyzed by two independent reviewers through a consensus approach. Data collection continued until thematic saturation was reached. Domains were then identified from interviews and PROMs (Dizziness Handicap Inventory, Hospital Anxiety and Depression Scale, EQ-5D-5L) using the ICF linking process. The analysis comprised three stages: (1), documenting the full spectrum of UVH symptoms and impacts from interviews, (2) reporting domains and constructs based on interviews, (3) comparing domains identified from interviews with those from PROMs (DHI, HADS, EQ-5D-5L, analyzed separately).ResultsFifteen patients with chronic UVH were interviewed. Reported symptoms revealed 16 physical symptoms, four cognitive symptoms, and five emotions. Key challenges included driving difficulties, darkness, sleep problems, fear of falling, and discomfort in crowded environments. Patients adapted certain behaviors, such as moving slowly, using supports, and avoiding sudden movements. Regarding the ICF framework, the most frequently reported construct was Body functions, with key domains including emotional, vestibular, and hearing-related functions. Activities and participation focused on maintaining body position and family relationships, while environmental factors highlighted the impact of light and sound. Interviews identified key domains related to vision, memory, multitasking, and activities impacting quality of life that were often overlooked by the PROMs.ConclusionPatients with chronic UVH experience a wide spectrum of physical, cognitive, and emotional symptoms, resulting in significant limitations in daily life. The frequently used PROMs (DHI, HADS, and EQ-5D-5L) do not fully cover these symptoms and their impacts, which leave many aspects underrepresented. A tailored PROM for UVH may be needed, to better reflect the specific symptoms, behaviors and functional limitations related to chronic UVH.